The Efficiency of Farmers Group Association on Strengthening The Institutions of Community Food Distribution Program Stage in Yogyakarta Special Region 2014 - Eny Ivan's; Jangkung Handoyo Mulyo; Dwidjono Hadi Darwanto (Jurnal Ilmu Pertanian, 2017)
In protecting and empowering the farmers, farmers group, and farmers group association (Gapoktan) from falling prices of grain and rice at harvest time and food accessibility problems, the government through the Ministry of Agriculture and Food Security Agency implemented the Strengthening the Institutions of Community Food Distribution Program (Strengthening-LDPM). This research was aimed to analyse the level of efficiency and to identify factors influencing the efficiency of Gapoktan in implementing the Strengthening-LDPM by involving 40 Gapoktan post-independence. The data used in this research were primary and secondary data, drawn from stockopname reports in 2014. This research used DEA (Data Envelopment Analysis) analysis, assuming that CRS (Constant Return to Scale) and VRS (Variable Return to Scale) using output-oriented assumptions. In addition, factors affecting the efficiency were analysed using multiple regression OLS (Ordinary Least Square). Based on DEA-CRS approach, as much as 37.5% Gapoktan were efficient and 62.5% Gapoktan were inefficient. Whereas with the approach of the DEA-VRS, 50% Gapoktan were efficient and 50% Gapoktan were inefficient. The average age of Gapoktan board, total volume of grain or rice sales, total volume of food reserve, and total loan interest affect significantly in increasing the efficiency of Gapoktan in running the strengthening-LDPM Program.